2014
DOI: 10.1007/s00270-013-0803-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Ablation Effects of a Microbubble-Enhancing Contrast Agent (“SonoVue”) in the Treatment of Uterine Fibroids With High-Intensity Focused Ultrasound: A Randomized Controlled Trial

Abstract: Based on the results of this randomized controlled trial, SonoVue could be safely used to enhance the effects of HIFU treatment for uterine fibroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Kennedy et al have used CEUS to evaluate the extent of ablation after HIFU treatment of liver tumor [8]. Recently, some studies showed that SonoVue may play a role in enhancing the effect of HIFU ablation for uterine fibroids [19,20]. However, to the best of our knowledge, no one has compared the intraprocedure CEUS results of HIFU with that of MRI.…”
Section: Discussionmentioning
confidence: 95%
“…Kennedy et al have used CEUS to evaluate the extent of ablation after HIFU treatment of liver tumor [8]. Recently, some studies showed that SonoVue may play a role in enhancing the effect of HIFU ablation for uterine fibroids [19,20]. However, to the best of our knowledge, no one has compared the intraprocedure CEUS results of HIFU with that of MRI.…”
Section: Discussionmentioning
confidence: 95%
“…10,11 Based on the results of the experimental study, we performed a clinical study to investigate which time point after administration of SonoVue is the most effective and safest in the treatment of uterine fibroids with HIFU. In this study, we started to treat patients at 1, 3 or 5 minutes after administration of SonoVue.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Briefly, every patient was carefully positioned prone on the HIFU table. The anterior abdominal wall was in contact with degassed water.…”
Section: Usghifu After Administration Of Sonovuementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the authors suggested that the encapsulated MBs enhanced the outcome of HIFU ablation and can be used to assess the extent of treatment. In a similar study, Jiang et al (2014) evaluated the clinical value of encapsulated MBs in the treatment of uterine fibroids with HIFU ablation in patients with a history of pelvic operation. A total of 80 patients with solitary uterine fibroids at a single center were randomly assigned to a control or SonoVue group (half-and-half) and were treated with HIFU.…”
Section: Preclinical Evaluation Of Cavitation-enhanced Thermal Effectsmentioning
confidence: 99%